Pembiasaan Shalat Dhuha Berjamaah dalam Mengembangkan Nilai Agama dan Budi Pekerti Pada Anak Usia Dini - Aren Rose Juwa Abdul; Lilif Muallifatul Khorida Filasofa; Muslam (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The habituation of religious practices of dhuha prayer in congregation at RA Bina Mutiara Hati aims to create Islamic early childhood, noble character and produce the potential of early childhood as human resources (HR) based on the Qur'an. This study aims to examine how the implementation of habituation of dhuha prayer in congregation in developing religious values and character of early childhood in RA Bina Mutiara Hati. This research uses descriptive qualitative research with data collection through observation techniques, structured interviews and documentation. The results showed that the habituation of dhuha prayers in congregation had a major influence on the development of children's religious values and character, namely: when hearing the dhuhur call to prayer, children immediately rushed to take ablution and go to the mosque, children were also more attentive to personal hygiene after knowing about unclean and holy, and the habituation of dhuha prayers made children grateful and care for all creatures created by God by loving their friends. The habituation of dhuha prayer in congregation has a major effect in developing children's religious values and character, but there are still some children whose religious values and character have not developed according to the indicators, namely children who are not serious when habituation is carried out and Children with Special Needs (ABK) with speech delay and ADHD characteristics. Teachers at RA Bina Mutiara Hati are expected to improve methods in the practice of habituation of dhuha prayer so that the development of religious values and character of all children can develop well.